POSSIBILIDADES E ESTRATÉGIAS PEDAGÓGICAS NO ENSINO DE CIÊNCIAS E BIOLOGIA: UMA CONTEXTUALIZAÇÃO À LUZ DOS LIVROS DIDÁTICOS - Guerin Junior, Claudi; Cunha, Fernando Icaro Jorge; Dinardi, Ailton Jesus [UNESP] (Univ Federal Mato Grosso Sul, 2023)
Textbooks can become excellent allies in the teaching and learning process, as long as they address issues related to the school context and contribute to a methodology focused on student protagonist. In view of this statement, this article aims to analyze a sample of Science textbooks regarding the insertion of pedagogical activities that facilitate Science Teaching. This study can be considered qualitative research, of the exploratory type, because from a collection of textbooks on Sciences, categories of analysis of the textbook were elaborated regarding the relationship between theory and practice and the search for activities such as didactic games and practical classes, that could have a positive impact on teaching practice. The data collected show us that all the books in the collection dedicate a space to a didactic activity to be carried out in a formal and non-formal teaching space, however, in the analysis of the same, no didactic game was found, and the game can be an artifice. facilitator of learning as a viable alternative for the improvement of the teaching and learning process. Based on the absence of didactic games in the textbook collection, a booklet was built, available in print and digital format, with suggestions of playful activities that facilitate learning, making classes more interactive and dynamic.
Keywords: Activities; Contextualization; Biology and Science